Effects of cottonseed meal on growth performance, small intestinal morphology, digestive enzyme activities, and serum biochemical parameters of geese. (7th January 2019) - Yu, J; Wang, Z Y; Yang, H M; Xu, L; Wan, X L
ABSTRACT: Cottonseed meal (CSM), an oil industry by-product, is an attractive alternative protein source in poultry diets. To investigate the effects of CSM on growth performance, small intestinal morphology, digestive enzyme activities, and serum biochemical parameters of geese, a total of 300 healthy, 28-day-old, male Jiangnan geese were randomly divided into 5 treatments, with 6 pens of 10 geese each. Five isonitrogenous and isocaloric experimental diets were formulated to produce diets in which 0% (control), 25% (CSM25 ), 50% (CSM50 ), 75% (CSM75 ), and 100% (CSM100 ) of protein from soybean meal was replaced by CSM (corresponding to 0, 6.73, 13.46, 20.18, and 26.91% CSM in the feed, respectively). At 28, 42, and 70 d, BW and feed intake for each pen were measured. Blood, small intestine, and chyme samples were collected at 70 d. The results showed that dietary 13.46% CSM or more decreased BW at 42 d and ADG from 28 to 42 d but increased the feed/gain ratio (F/G) from 28 to 42 d ( P < 0.05). From 42 to 70 d, geese in the CSM groups had higher ADFI and ADG than those of the control group ( P < 0.05). Geese in the CSM75 and CSM100 groups had a higher ADG from 28 to 70 d and BW at 70 d and a lower F/G from 42 to 70 d than those of the control group ( P < 0.05). Dietary 6.73% CSM also improved ADFI from 28 to 70 d ( P < 0.05). Compared to the control, geese in the CSM groups had decreased pepsin and lipase activities, and those in the CSM25, CSM50, and CSM75 groups had increased villus height in the jejunum at 70 d ( P < 0.05). All groups had similar concentrations of total protein, blood urea nitrogen, uric acid, cholesterol, triglyceride, calcium, and phosphorus in serum ( P > 0.05). In conclusion, excessive use of CSM (>6.73%) decreased growth performance at an early age (28 to 42 d) in geese, whereas 6.73 to 26.91% CSM in feed improved growth performance from 28 to 70 d.